The Effect of Dysmenorrhea Exercise on Reducing Menstrual Pain Felt by Adolescent Girls - I Gusti Ayu Ratih Agustini (Babali Health, 2022)
Introduction: Dysmenorrhea can be overcome in one way, namely dysmenorrhea exercise. This exercise is useful for improving blood flow therefore it can increase the endorphins hormone through movements that make you feel comfortable and relaxed. The purpose of this study was to analyze the effect of dysmenorrhea exercise on reducing menstrual pain felt by adolescent girls. Methods: This study was pre-experimental research with one group pretest-posttest design. The sampling technique used was total sampling consisting of 35 adolescents girl with dysmenorrhea. Data was collected using an instrument in the form of a numerical rating scale (NRS). This research was conducted in January - March 2022 in the village of Jineng Dalem Buleleng. Results: The results of the Wilcoxon Signed Ranks statistical test in adolescents who were given the intervention of dysmenorrhea exercise therapy showed that there were no respondents who increased menstrual pain. This shows that after the intervention, 35 respondents experienced a decrease in menstrual pain. The statistical results obtained that the calculated Z value is 5.189 > from the z table value of 1.960 with a p value of 0.001 <0.05. Conclusion: Therefore it can be concluded that there was an effect of dysmenorrhea exercise on reducing menstrual pain felt by adolescent girls in Jineng Dalem Village, Buleleng District. Based on the results of this study, it is hoped that adolescents who experience dysmenorrhea can use non-pharmacological therapies such as dysmenorrhea exercises to reduce menstrual pain.